Kedudukan Akun Trading sebagai Objek Waris Menurut Perspektif Hukum di Indonesia dan Hukum Islam - Aqiilah Dahayu Aristawati; Muhammad Yogi Galih Permana (BUSTANUL FUQAHA: Jurnal Bidang Hukum Islam, 2023)
The state of cyberspace or the virtual world is increasingly advanced because globalization conditions have now reached 5.0, which is able to minimize economic problems, with the help of existing technological developments so that trading can be realized. Consideration of the law in its use and even the position of the trading account as an inheritance object is still something that has not been answered in detail. This research aims to determine the position of trading accounts as objects of inheritance according to Indonesian law and Islamic law. With normative research methods, this research uses a statutory approach. The results of this research found that trading in Indonesian law is permitted, but there is still an overlap in Islamic law which prohibits trading of any kind. Regarding the position of the trading account itself, it is allowed to become an object of inheritance because the trading account is a digital object, where digital objects are included in the type of object that can be used as an object of inheritance, in accordance with legal provisions in Indonesia. According to Islamic law, the position of a trading account as an object of inheritance requires differentiation of assets.